The self and shame in the Malay context: a qualitative study - Aknouche, Nadjet; Noor, Noraini M. (Pearson, 2012)
The present research investigated the role of the self in steering different forms of shame, with distinct behavioural outcomes in contemporary Malay culture. The findings of this study are consistent with those of mainstream research indicating that shame is detrimental. However, the findings departed sharply from previous research in distinguishing between an anaemically deficient shame (shamelessness) and an exceedingly surfeited shame (global/specific)and identifying a healthy kind of shame. The role of the self in shame experiences raises the question of how shame contributes to the self (e.g. Barrett, 1995). We believe that the relationship between the two constructs is bidirectional and that assigning regulatory functions to a generic shame (e.g. Barrett, 1995; Gilbert, 1997) obstructs understanding the contribution of shame to the self. Shame as a multifaceted construct can have different effects on the self, depending on what kind of shame is experienced.